Water-based resin composition
The aqueous resin composition with acid-modified polyolefin resin and tailored (meth)acrylic ester copolymers addresses low peel strength and solvent issues, ensuring strong adhesion and compatibility for polyolefin substrates while minimizing environmental impact.
Patent Information
- Application Number
- JP2021513563
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-04-11
- Filing Date
- 2020-03-26
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2040-03-26
AI Technical Summary
Existing aqueous resin compositions for polyolefin substrates face challenges with low peel strength and poor adhesion when baked at high temperatures, and they often require organic solvents, leading to environmental concerns.
An aqueous resin composition containing acid-modified polyolefin resin and specific (meth)acrylic ester copolymers with varying carbon atom counts in their ester moieties, along with optional surfactants and basic compounds, is formulated to enhance adhesion and compatibility without using organic solvents.
The composition achieves high peel strength and excellent adhesion to polyolefin substrates even at 80°C, with improved compatibility and reduced solvent use, facilitating a more environmentally friendly manufacturing process.
Smart Images

Figure 0007616049000001 
Figure 0007616049000002
Abstract
Description
[Technical field]
[0001] The present invention relates to an aqueous resin composition having high adhesion to polyolefin substrates. [Background technology]
[0002] In general, polyolefin resins such as polypropylene, polyethylene, ethylene-propylene copolymers, ethylene-propylene-diene copolymers, and poly(4-methyl-1-pentene) are relatively inexpensive and have excellent properties, such as chemical resistance, water resistance, heat resistance, etc., and are used in a wide range of fields as materials for automobile parts, electric parts, building materials, packaging films, etc. However, polyolefin resins are crystalline and non-polar, and therefore it is difficult to apply coating or adhesion to them.
[0003] For coating or bonding such poorly adhesive polyolefin-based resins, chlorinated polyolefins, which have strong adhesive power to polyolefin-based resins, have conventionally been used as binder resins (see Patent Documents 1 and 2). In order to compensate for the drawbacks of chlorinated polyolefins, such as poor adhesion to substrates or limited objects to be bonded, chlorinated polyolefins are mixed with acrylic, urethane, or polyester resins, or these resins are graft-polymerized onto chlorinated polyolefins to form binder compositions, which are then used for coating or bonding (see Patent Documents 3 and 4).
[0004] However, most of these binder compositions are used in a form dissolved in an organic solvent such as toluene or xylene, and a large amount of the organic solvent is released into the atmosphere during coating, which is undesirable from the environmental and hygienic standpoints.
[0005] In view of this, aqueous resin compositions containing polyolefin resins that do not contain organic solvents have been proposed (see Patent Documents 5 and 6). However, in these compositions, the polyolefin resin itself has low polarity, and when mixed with acrylic, urethane, epoxy, or polyester resins, it is difficult to make them compatible, so that the expected physical properties are not exhibited.
[0006] In response to these problems, an emulsion production method has been proposed in which polyolefin is dissolved in an acrylic monomer, and the monomer is polymerized after phase inversion emulsification (see Patent Documents 7 and 8). These production methods can reduce costs by shortening the solvent removal step, and can provide aqueous resin compositions that have excellent compatibility with other resins because they contain acrylic. [Patent Document 1] Japanese Patent Application Publication No. 59-75958 [Patent Document 2] Japanese Patent Application Publication No. 60-99138 [Patent Document 3] Japanese Patent Application Publication No. 6-16746 [Patent Document 4] Japanese Patent Application Publication No. 8-12913 [Patent Document 5] Japanese Patent Application Publication No. 6-256592 [Patent Document 6] JP 2004-107539 A [Patent Document 7] Japanese Patent Application Publication No. 6-80738 [Patent Document 8] JP 2010-001334 A DISCLOSURE OF THEINVENTION [Problem to be solved by the invention]
[0007] On the other hand, since half of the resin content of these compositions is acrylic, there is a problem that the peel strength with the polyolefin substrate is reduced. The object of the present invention is to solve the above problems, and to provide an aqueous resin composition for use in a coating material, ink, adhesive, sealant or primer that is a mixture of polyolefin and acrylic and that exhibits high peel strength even when baked at 80°C on a polyolefin substrate and does not impair adhesion even when it contains an acrylic component. [Means for solving the problem]
[0008] The present inventors have found that the above-mentioned problems can be solved by an aqueous resin composition containing an acid-modified polyolefin resin (A) and a (meth)acrylic acid ester copolymer (B) containing a (meth)acrylic acid ester (B1) whose ester moiety is a hydrocarbon group having 12 or more carbon atoms, and a (meth)acrylic acid ester (B2) whose ester moiety is a hydrocarbon group having 11 or less carbon atoms.
[0009] The present invention is as described below.
[0010] An aqueous resin composition containing an acid-modified polyolefin resin (A) and a (meth)acrylic acid ester copolymer (B), characterized in that the acid-modified polyolefin resin (A) contains an unsaturated carboxylic acid or its anhydride in the range of 0.5 to 10.0 mass %, and the (meth)acrylic acid ester copolymer (B) contains a (meth)acrylic acid ester (B1) having an ester moiety with 12 or more carbon atoms and a (meth)acrylic acid ester (B2) having an ester moiety with 11 or less carbon atoms.
[0011] It is preferred that the (meth)acrylic acid ester copolymer (B) further contains one or more polar group-containing monomers (B3) selected from a polar group-containing (meth)acrylic acid ester, (meth)acrylic acid, and (meth)acrylamide.
[0012] In addition to the acid-modified polyolefin resin (A) and the (meth)acrylic acid ester copolymer (B), it is preferable to contain either or both of a surfactant and a basic compound, and the content of the (meth)acrylic acid ester copolymer (B) per 100 parts by mass of the acid-modified polyolefin resin (A) is preferably in the range of 40 to 250 parts by mass.
[0013] The (meth)acrylic acid ester copolymer (B) preferably has a mass ratio of the (meth)acrylic acid ester (B1) in which the ester moiety is a hydrocarbon group having 12 or more carbon atoms to the (meth)acrylic acid ester (B2) in which the ester moiety is a hydrocarbon group having 11 or less carbon atoms within a range of 70 / 30 to 20 / 80.
[0014] The (meth)acrylic acid ester copolymer (B) preferably has a glass transition temperature (Tg) within the range of -40°C to 80°C, and the acid-modified polyolefin resin (A) preferably has a melting point of 90°C or lower as measured by a differential scanning calorimeter (DSC).
[0015] Any of the above-described aqueous resin compositions can be used as coating materials, inks, adhesives, sealants, or primers for polyolefin films, sheets, or molded articles. Effect of the Invention
[0016] The aqueous resin composition of the present invention exhibits excellent adhesion and water resistance to polyolefin substrates even when baked at 80°C, and exhibits high peel strength equivalent to that of acid-modified polyolefin resin alone, despite containing an acrylic resin. In addition, the aqueous resin composition of the present invention has good compatibility with various polar resins, and does not contain organic solvents, so that it can be obtained in a production process that shortens the solvent removal process, and can be used for paints, inks, adhesives, sealants, and primers. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] The present invention will be described in detail below.
[0018] The present invention is an aqueous resin composition containing an acid-modified polyolefin resin (A) and a (meth)acrylic acid ester copolymer (B), characterized in that the acid-modified polyolefin resin (A) contains an unsaturated carboxylic acid or anhydride thereof in the range of 0.5 to 10.0 mass %, and the (meth)acrylic acid ester copolymer (B) contains a (meth)acrylic acid ester (B1) whose ester moiety is a hydrocarbon group having 12 or more carbon atoms, and a (meth)acrylic acid ester (B2) whose ester moiety is a hydrocarbon group having 11 or less carbon atoms.
[0019] <Acid-modified polyolefin resin (A)> The acid-modified polyolefin resin (A) used in the present invention is obtained, for example, by graft copolymerizing at least one polyolefin selected from polypropylene, propylene-α-olefin copolymer, polyethylene, ethylene-α-olefin copolymer, poly-1-butene, and 1-butene-α-olefin copolymer with at least one selected from α,β-unsaturated carboxylic acids and acid anhydrides thereof.
[0020] Here, the propylene-α-olefin copolymer is a copolymer of propylene as a main component and an α-olefin. Examples of the α-olefin include α-olefins having 2 or 4 to 20 carbon atoms, such as ethylene, 1-butene, 1-pentene, 1-hexene, 1-heptene, 1-octene, 1-decene, 1-dodecene, 1-hexadecene, and 4-methyl-1-pentene. The content of the propylene component in the propylene-α-olefin copolymer is preferably 50 mol% or more, more preferably 70 mol% or more. When the content of the propylene component is 50 mol% or more, the adhesion to the polypropylene substrate is good.
[0021] The ethylene-α-olefin copolymer is a copolymer of ethylene with an α-olefin as the main component. Examples of the α-olefin include α-olefins having 3 to 20 carbon atoms, such as propylene, 1-butene, 1-pentene, 1-hexene, 1-heptene, 1-octene, 1-decene, 1-dodecene, 1-hexadecene, and 4-methyl-1-pentene. The content of the ethylene component in the ethylene-α-olefin copolymer is preferably 75 mol% or more. When the content of the ethylene component is 75 mol% or more, the adhesion to the polyethylene substrate is good.
[0022] The 1-butene-α-olefin copolymer is a copolymer of 1-butene as a main component and an α-olefin. Examples of the α-olefin include α-olefins having 2 to 3 or 5 to 20 carbon atoms, such as ethylene, propylene, 1-pentene, 1-hexene, 1-heptene, 1-octene, 1-decene, 1-dodecene, 1-hexadecene, and 4-methyl-1-pentene. The content of the 1-butene component in the 1-butene-α-olefin copolymer is preferably 65 mol% or more. When the content of the 1-butene component is 65 mol% or more, the adhesion to a polypropylene substrate or a poly-1-butene substrate is good.
[0023] Examples of the α,β-unsaturated carboxylic acid or its acid anhydride to be graft-copolymerized onto the polyolefin include maleic acid, maleic anhydride, fumaric acid, citraconic acid, citraconic anhydride, mesaconic acid, itaconic anhydride, aconitic acid, aconitic anhydride, himic anhydride, etc. Among these, maleic anhydride and itaconic anhydride are preferred.
[0024] The content of the α,β-unsaturated carboxylic acid component or its acid anhydride component in the acid-modified polyolefin resin (A) is 0.5 to 10 mass %, preferably 0.7 mass % or more, more preferably 1 mass % or more, more preferably 5 mass % or less, and even more preferably 3 mass % or less. When the content of the α,β-unsaturated carboxylic acid component or its acid anhydride component is within this range, phase inversion emulsification becomes easy, and the water resistance of the coating film obtained from the aqueous resin composition becomes good.
[0025] Examples of a method for graft copolymerizing at least one selected from an α,β-unsaturated carboxylic acid and an acid anhydride thereof onto a polyolefin include known methods such as a method in which the polyolefin is heated to above its melting point in the presence of a radical generator to cause a reaction (melt method) and a method in which the polyolefin is dissolved in an organic solvent and then heated and stirred in the presence of a radical generator to cause a reaction (solution method).
[0026] The weight average molecular weight of the acid-modified polyolefin resin (A) used in the present invention, as measured by high-temperature GPC (gel permeation chromatography), is preferably 3,000 to 200,000. More preferably, it is 10,000 or more, even more preferably 30,000 or more, and particularly preferably 45,000 or more. Also, it is more preferably 150,000 or less, and even more preferably 120,000 or less. When it is within the above range, the dissolution of the acid-modified polyolefin in the (meth)acrylic acid ester (B1) and the (meth)acrylic acid ester (B2) becomes good, and phase inversion emulsification becomes easy. Also, the cohesive force of the resin becomes sufficient, and the adhesive force becomes good.
[0027] The measurement of the weight average molecular weight by high temperature GPC can be performed by a known method using a commercially available device with orthodichlorobenzene as a solvent and polystyrene as a standard substance. Specifically, the measurement is performed using a GPC150-C Plus model manufactured by Waters at 140°C using orthodichlorobenzene as a solvent. The columns used are GMH6-HT and GMH6-HTL manufactured by Tosoh Corporation. The weight average molecular weight is calculated using polystyrene with a known molecular weight as a standard substance.
[0028] The acid-modified polyolefin resin (A) may be further modified by chlorination. The chlorinated polyolefin is preferably an acid-modified chlorinated polyolefin obtained by chlorinating the acid-modified polyolefin resin. When the acid-modified polyolefin resin (A) is chlorinated, the chlorine content is preferably 5% by mass or more in terms of solution stability and adhesion between the polyolefin substrate and the resin substrate or metal substrate, more preferably 8% by mass or more, even more preferably 10% by mass or more, particularly preferably 12% by mass or more, and most preferably 14% by mass or more. When it is 5% by mass or more, the solution stability is good and emulsification is easy. The upper limit is preferably 40% by mass or less, more preferably 38% by mass or less, even more preferably 35% by mass or less, particularly preferably 32% by mass or less, and most preferably 30% by mass or less. When it is 40% by mass or less, the crystallinity of the acid-modified chlorinated polyolefin is high, and the adhesive strength is likely to be strong.
[0029] The chlorine content of the acid-modified chlorinated polyolefin can be measured by titration in accordance with JIS K-7229-1995.
[0030] The melting point of the acid-modified polyolefin resin (A) in the present invention as measured by a differential scanning calorimeter (hereinafter referred to as DSC) is preferably 90° C. or less, more preferably 85° C. or less, and particularly preferably 80° C. or less. When the melting point is within the above range, the film-forming property in baking at 80° C. is favorable, and the adhesion to polyolefin substrates, water resistance, and peel strength are good.
[0031] The melting point measurement by DSC in the present invention can be performed according to JIS K7121-2012, for example, under the following conditions. Using a DSC measuring device (manufactured by Seiko Denshi Kogyo), about 5 mg of a sample is heated and melted at 150°C for 10 minutes, cooled at a rate of 10°C / min, stably held at -50°C, and then heated at a rate of 10°C / min to 150°C to melt, and the melting peak temperature is measured, and the temperature is evaluated as the melting point. The melting points in the examples described below are measured under the above-mentioned conditions.
[0032] <(Meth)acrylic acid ester copolymer (B)> The (meth)acrylic acid ester copolymer (B) used in the present invention contains, as copolymerization components, a (meth)acrylic acid ester (B1) whose ester moiety is a hydrocarbon group having 12 or more carbon atoms and a (meth)acrylic acid ester (B2) whose ester moiety is a hydrocarbon group having 11 or less carbon atoms. Hereinafter, they are also simply referred to as (B1) and (B2).
[0033] By containing (B1) and (B2), the acid-modified polyolefin resin (A) can be sufficiently dissolved, phase inversion emulsification becomes easy, and in addition, adhesion to polyolefin substrates becomes good despite the inclusion of an acrylic component. In addition, the affinity with resins other than polyolefins becomes high, and compatibility with other resins in the coating film becomes good.
[0034] The content of the (meth)acrylic acid ester copolymer (B) per 100 parts by mass of the acid-modified polyolefin resin (A) is preferably in the range of 40 to 250 parts by mass, more preferably in the range of 80 to 200, and even more preferably in the range of 100 to 150. When the content of (B) is within the range of 40 to 250, phase inversion emulsification of the acid-modified polyolefin resin (A) becomes easy, and the adhesion to the polyolefin resin substrate becomes good.
[0035] <(Meth)acrylic acid ester (B1)> Examples of the (meth)acrylic acid ester (B1) used in the present invention in which the ester moiety is a hydrocarbon group having 12 or more carbon atoms include dodecyl (meth)acrylate {lauryl (meth)acrylate}, tridecyl (meth)acrylate, tetradecyl (meth)acrylate, pentadecyl (meth)acrylate, hexadecyl (meth)acrylate, heptadecyl (meth)acrylate, stearyl (meth)acrylate, isostearyl (meth)acrylate, nonadecyl (meth)acrylate, icosyl (meth)acrylate, and henicosyl (meth)acrylate. Examples of the acrylic monomer include acrylic monomers such as acrylate, behenyl (meth)acrylate, tricosyl (meth)acrylate, tetracosyl (meth)acrylate, pentacosyl (meth)acrylate, hexacosyl (meth)acrylate, heptacosyl (meth)acrylate, octacosyl (meth)acrylate, nonacosyl (meth)acrylate, triacontyl (meth)acrylate, hentriacontyl (meth)acrylate, dotriacontyl (meth)acrylate, tetratriacontyl (meth)acrylate, and pentatriacontyl (meth)acrylate. The hydrocarbon group may be linear or branched, or may contain a cyclic structure. These monomers may be used alone or in combination of two or more.
[0036] The number of carbon atoms in the ester portion of the (meth)acrylic acid ester (B1) is 12 or more and preferably 35 or less, and more preferably 18 or less. When it is 12 or more and 35 or less, the solubility of the acid-modified polyolefin resin (A) and the polymerizability during emulsion polymerization become favorable.
[0037] <(Meth)acrylic acid ester (B2)> Examples of the (meth)acrylic acid ester (B2) used in the present invention in which the ester moiety is a hydrocarbon group having 11 or less carbon atoms include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, iso-propyl (meth)acrylate, n-butyl (meth)acrylate, iso-butyl (meth)acrylate, tert-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, cyclohexyl (meth)acrylate, tert-butylcyclohexyl (meth)acrylate, isobornyl (meth)acrylate, and dicyclopentanyl (meth)acrylate. These monomers can be used alone or in combination of two or more.
[0038] The number of carbon atoms in the ester portion of the (meth)acrylic acid ester (B2) is preferably from 1 to 10, and more preferably from 8 to 10. When the number of carbon atoms is from 1 to 10, the solubility of the acid-modified polyolefin becomes favorable, and phase inversion emulsification and emulsion polymerization become easy.
[0039] The mass ratio of the (meth)acrylic acid ester (B1) in which the ester moiety is a hydrocarbon group having 12 or more carbon atoms and the (meth)acrylic acid ester (B2) in which the ester moiety is a hydrocarbon group having 11 or less carbon atoms contained in the (meth)acrylic acid ester copolymer (B) used in the present invention is preferably within a range of 70 / 30 to 20 / 80. More preferably, it is 60 / 40 to 40 / 60. When it is within the above range, the solubility of the acid-modified polyolefin resin (A) is increased, and phase inversion emulsification becomes easy. In addition, the affinity between the (meth)acrylic acid ester copolymer and the polyolefin substrate is improved, and the adhesion to the polyolefin substrate becomes good.
[0040] <Polar group-containing monomer (B3)> The (meth)acrylic acid ester copolymer (B) used in the present invention may further be copolymerized with a polar group-containing monomer (B3). (Hereinafter, also simply referred to as (B3)). (B3) is different from (B1) and (B2), and examples of (B3) include (meth)acrylic acid esters having a polar group in the ester moiety, (meth)acrylic acid, and (meth)acrylamide, and one or more selected from these may be used. Examples of the polar group of the acrylic acid ester having a polar group in the ester moiety include a hydroxyl group, a carboxyl group, a phosphoric acid group, an amino group, an amide group, an ether group, and an epoxy group. Among these, an amide group and a hydroxyl group are preferably used, and a hydroxyl group is more preferably used. Examples of acrylic acid esters having a polar group in the ester moiety include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, dicyclopentenyl (meth)acrylate, glycidyl (meth)acrylate, methyl glycidyl (meth)acrylate, 3,4-epoxycyclohexanemethyl methacrylate, tetrahydrofurfuryl (meth)acrylate, polyethylene glycol mono(meth)acrylate, polyethylene glycol di(meth)acrylate, polypropylene glycol mono(meth)acrylate, polypropylene glycol di(meth)acrylate, polytetramethylene glycol mono(meth)acrylate, polytetramethylene glycol di(meth)acrylate, dimethylaminoethyl (meth)acrylate, diethylaminoethyl (meth)acrylate, etc. Examples of acrylamides include (meth)acrylamide, dimethyl(meth)acrylamide, diethyl(meth)acrylamide, dimethylaminopropyl (meth)acrylamide, etc. It is preferable to use one or more of these, and more preferable to use two or more of these having the same polar group. By using these (B3) in combination with (B1) and (B2), the adhesion to polar substrates and topcoat paints becomes better than when only (B1) and (B2) are used.Furthermore, (B3) alone has poor solubility in the acid-modified polyolefin resin (A), but when used in combination with (B1) and (B2), it exhibits good compatibility with the acid-modified polyolefin resin (A).
[0041] The (B3) used in the present invention is preferably used in an amount of 1 to 40% by mass relative to the (meth)acrylic acid ester copolymer (B). More preferably, it is 2% by mass or more, even more preferably, 4% by mass or more, and particularly preferably, 6% by mass or more. Also, it is more preferably 30% by mass or less, even more preferably, 25% by mass or less, and most preferably, 20% by mass or less. Within the above range, the solubility of the acid-modified polyolefin (A) increases, and phase inversion emulsification becomes easy. In addition, the polar group content in the (meth)acrylic acid ester copolymer (B) becomes suitable, and thus the adhesion of the target composition to polyolefin substrates, polar substrates, and topcoat coatings becomes good.
[0042] In this application, "(meth)acrylate" means "acrylate or methacrylate", "(meth)acrylic acid" means "acrylic acid or methacrylic acid", "(meth)acryloyl group" means "acryloyl group or methacryloyl group", and "(meth)acrylamide" means "acrylamide or methacrylamide".
[0043] Furthermore, the (meth)acrylic acid ester copolymer (B) of the present invention may contain a polymerizable monomer other than (B1), (B2), and (B3). Examples of the polymerizable monomer other than (B1), (B2), and (B3) include styrene-based monomers such as styrene, α-methylstyrene, paramethylstyrene, and divinylbenzene. Furthermore, examples of monomers that can be used in combination with the above include vinyl acetate. These monomers can be used alone or in combination of two or more.
[0044] The glass transition temperature (Tg) of the (meth)acrylic acid ester copolymer (B) is preferably within the range of -40°C to 80°C. It is more preferably -30°C or higher, and even more preferably -20°C or higher. It is more preferably 60°C or lower, and even more preferably 50°C or lower. By being within the above range, the flexibility of the coating film becomes suitable, the bleeding of other components is suppressed, and the water resistance and the appearance of the coating film become good. In addition, the film formability of the coating film when baked at 80°C becomes suitable, and the adhesion to the polyolefin substrate, water resistance, and peel strength become good.
[0045] In order to design a (meth)acrylic acid ester copolymer (B) having a desired Tg, the mixing ratio of the (meth)acrylic acid ester monomer and the polar group-containing monomer is determined taking into consideration the glass transition temperature of the homopolymer (hereinafter also referred to as "Tg of the homopolymer") obtained when each of the (meth)acrylic acid ester monomer and the polar group-containing monomer is homopolymerized.
[0046] Specifically, the Tg of the (meth)acrylic acid ester copolymer (B) can be calculated using the formula (FOX formula) for calculating the theoretical Tg of a (meth)acrylic acid ester copolymer. 1 / Tg=C1 / Tg1+C2 / Tg2+...+Cn / Tgn:(FOX formula) [In the calculation formula (FOX formula), Tg is the theoretical Tg of the (meth)acrylic acid ester copolymer, Cn is the weight ratio of monomer n contained in the monomer mixture of the (meth)acrylic acid ester copolymer (B), Tgn is the Tg of the homopolymer of monomer n, and n is the number of monomers constituting the (meth)acrylic acid ester copolymer (B), and is a positive integer.] For example, lauryl methacrylate (Tg 208.15K, 46% by mass) as (B1), cyclohexyl methacrylate (Tg 339.15K, 46% by mass) as (B2), 2-hydroxyethyl methacrylate (Tg 328.15K, 4% by mass) as (B3), The calculation formula when using 4-hydroxybutyl acrylate (Tg 233.15K, 4% by mass) is as follows. The calculated theoretical Tg of the copolymer is 259.1 (K), which converts to -14.1°C. 1 / Tg=0.46 / 208.15+0.46 / 339.15+0.04 / 328.15+0.04 / 233.15 The Tg in the present invention is the theoretical Tg (° C.) calculated from the above formula.
[0047] The Tg of the homopolymer of the (meth)acrylic acid ester monomer and the polar group-containing monomer can be a value described in the literature. For example, the following literature can be referred to: Kyoeisha Chemical's (meth)acrylic acid ester catalog, Mitsubishi Chemical's acrylic ester catalog; and Kyozo Kitaoka, "New Polymer Library 7, Introduction to Synthetic Resins for Paints," Polymer Publishing Association, 1997, pp. 168-169.
[0048] <Surfactant> The aqueous resin composition according to the present invention can contain a surfactant within a range that does not impair the performance of the present invention. Examples of the surfactant include nonionic surfactants, anionic surfactants, cationic surfactants, and amphoteric surfactants. Among these, from the viewpoint of the particle size of the dispersed particles and the water resistance of the coating film obtained from the target composition, it is preferable to use a nonionic surfactant or anionic surfactant, and it is more preferable to use a nonionic surfactant.
[0049] Examples of nonionic surfactants include polyoxyethylene alkyl ethers, polyoxypropylene alkyl ethers, polyoxyethylene alkylphenyl ethers, polyoxypropylene alkylphenyl ethers, polyoxyethylene styrenated phenyl ethers, polyoxypropylene styrenated phenyl ethers, polyoxyethylene fatty acid esters, polyoxypropylene fatty acid esters, polyoxyethylene sorbitan fatty acid esters, polyoxypropylene sorbitan fatty acid esters, polyoxyethylene alkylamine ethers, polyoxypropylene alkylamine ethers, polyoxyethylene lanolin alcohol ethers, polyoxypropylene lanolin alcohol ethers, polyoxyethylene lanolin fatty acid esters, polyoxypropylene lanolin fatty acid esters, (polyoxyethyleneoxypropylene) block copolymers, etc. Examples of such surfactants include Emulmin series (manufactured by Sanyo Chemical Industries Co., Ltd.), Noigen series (manufactured by Daiichi Kogyo Seiyaku Co., Ltd.), and Brownon series (manufactured by Aoki Oil & Fat Industries Co., Ltd.).
[0050] In addition, as these nonionic surfactants, reactive surfactants having a polymerizable double bond in the molecule can also be used, such as ADEKA REASOAP ER-10, ER-20, ER-30, and ER-40 (all manufactured by ADEKA Corporation).
[0051] Examples of anionic surfactants include higher alkyl sulfates, alkylaryl polyoxyethylene sulfate salts, higher fatty acid salts, alkylaryl sulfonates, alkyl phosphate salts, etc. Examples of such surfactants include the Neocol series and the Hitenol series (manufactured by Daiichi Kogyo Seiyaku Co., Ltd.).
[0052] In addition, reactive surfactants having a polymerizable double bond in the molecule can also be used as these anionic surfactants. Examples of such surfactants include ADEKA REASOAP NE-10, NE-20, NE-30, NE-40, and SE-10N (all manufactured by ADEKA Corporation), AQUALON RN-20, RN-30, RN-50, HS-10, and HS-20 (all manufactured by Daiichi Kogyo Seiyaku Co., Ltd.), ELEMINOL JS-2, and ELEMINOL RS-30 (all manufactured by Sanyo Chemical Industries, Ltd.).
[0053] The above surfactants can be used alone or in combination of two or more.
[0054] In the present invention, the surfactant is preferably used in an amount of 5 to 60 parts by mass per 100 parts by mass of the acid-modified polyolefin resin (A) from the viewpoints of ease of phase inversion emulsification and water resistance of the coating film. More preferably, the amount is 40 parts by mass or less, and even more preferably, 30 parts by mass or less. Also, more preferably, the amount is 20 parts by mass or less.
[0055] <Basic compounds> In the present invention, a basic compound may be further contained. In addition, a basic compound can be used in the production of the aqueous resin composition of the present invention, and for example, a basic compound can be made to coexist when the acid-modified polyolefin resin (A) is subjected to phase inversion emulsification. By making this compound exist in the system, it is possible to improve the dispersibility of the acid-modified polyolefin resin (A). Examples of the basic compound include inorganic basic compounds such as sodium hydroxide, potassium hydroxide, sodium carbonate, potassium carbonate, and ammonium carbonate; amines such as triethylamine, N,N-dimethylethanolamine, aminoethanolamine, N-methyl-N,N-diethanolamine, isopropylamine, iminobispropylamine, ethylamine, diethylamine, 3-ethoxypropylamine, 3-diethylaminopropylamine, sec-butylamine, propylamine, methylaminopropylamine, methyliminobispropylamine, 3-methoxypropylamine, monoethanolamine, diethanolamine, triethanolamine, morpholine, N-methylmorpholine, N-ethylmorpholine, 2-amino-2-methyl-1-propanol, and 2-dimethylamino-2-methyl-1-propanol; and ammonia.
[0056] The amount of the basic compound added is preferably 0.3 to 4.0 times the chemical equivalent, more preferably 0.7 to 2.5 times the chemical equivalent, of the carboxyl group of the acid-modified polyolefin resin (A). If the amount is less than 0.3 times the chemical equivalent, the effect of the presence of the basic compound may not be observed. On the other hand, if the amount exceeds 4.0 times the chemical equivalent, there is a risk that too much of the target composition will remain in the dried product.
[0057] The aqueous resin composition of the present invention can be obtained by dissolving the acid-modified polyolefin resin (A) in a mixed liquid of (B1) and (B2) without using an organic solvent, and then subjecting the mixture to phase inversion emulsification or polymerization reaction. Resin compositionThe organic solvent in is 0.5% by mass or less, more preferably 0.1% by mass or less, even more preferably 0.01% by mass or less, even more preferably 0.001% by mass or less, and particularly preferably 0% by mass. Since no organic solvent is used, there is no need to perform concentration and degassing, and the manufacturing process can be simplified, and the manufacturing cost and time can be reduced. Specifically, the (meth)acrylic acid ester solution of the acid-modified polyolefin resin (A) is subjected to phase inversion emulsification, and then the (meth)acrylic acid ester is polymerized to obtain the product. It is preferable to use a polymerization initiator to efficiently proceed with the polymerization reaction. As the polymerization initiator, it is preferable to use a polymerization initiator commonly used in normal emulsion polymerization in a conventional amount. Examples of such polymerization initiators include potassium persulfate, ammonium persulfate, hydrogen peroxide; azo initiators such as 4,4'-azobis(4-cyanovaleric acid), 2,2'-azobis[N-(2-carboxyethyl)-2-methylpropionamide], 2,2'-azobis[2-methyl-N-[2-(1-hydroxybutyl)]propionamide], and 2,2'-azobis[2-methyl-N-(2-hydroxyethyl)propionamide]; and peroxide initiators such as benzoyl peroxide, t-butylperoxy-2-ethylhexanoate, 1,1-bis(t-butylperoxy)-3,3,5-trimethylcyclohexane, t-butylperoxybenzoate, di-t-butylperoxide, t-butyl hydroperoxide, cumene hydroperoxide, p-menthane hydroperoxide, and diisopropylbenzene hydroperoxide. These can be used alone or in combination of two or more. Redox initiators can also be used, and examples thereof include those consisting of the above-mentioned polymerization initiators and reducing agents (e.g., sulfites, hydrogen sulfites, and salts of low ionic valence such as cobalt, iron, and copper).
[0058] The polymerization conditions may be appropriately set depending on the type of polymerizable monomer and polymerization initiator used, and the polymerization temperature is usually 20 to 100° C., preferably 50 to 90° C. The polymerization time is usually 1 to 8 hours. In order to rapidly proceed with the polymerization, it is preferable to replace the atmosphere in the polymerization system with an inert gas such as nitrogen gas.
[0059] The Z-average particle size of the resin particles in the aqueous resin composition obtained as described above is preferably 10 nm to 500 nm, more preferably 200 nm or less. If the average particle size exceeds 500 nm, defects may occur in the coating film after coating, adversely affecting various physical properties, and it is difficult to use the composition in top coat paints, which is not preferable.
[0060] The aqueous resin composition of the present invention can be used as a clear varnish as it is, but for the purpose of further improving the coating film performance, such as film-forming property, coating film hardness, weather resistance, flexibility, etc., various paint additives and other resin emulsions can be blended to the extent that the adhesion to polyolefin substrates is not inhibited. For example, film-forming assistants such as propylene glycol monopropyl ether, dipropylene glycol monomethyl ether, and butyl propylene diglycol, antifoaming agents, anti-sagging agents, wetting agents, and ultraviolet absorbers can be used. In particular, by blending and using an acrylic emulsion or a urethane emulsion, coating film performance such as weather resistance, water resistance, coating film strength, and flexibility can be improved.
[0061] Furthermore, the aqueous resin composition of the present invention may be appropriately added with a tackifier, for example, an aqueous dispersion of rosin, dammar, polymerized rosin, hydrogenated rosin, ester rosin, rosin-modified maleic acid resin, polyterpene resin, petroleum resin, cyclopentadiene resin, phenol resin, xylene resin, coumarone-indene resin, etc., as necessary, thereby improving the drying property of the coating film and the adhesion to the polyolefin substrate. The amount of addition is preferably 5 to 100 parts by mass of solid content, more preferably 10 to 50 parts by mass, relative to 100 parts by mass of solid content of the resin composition. If the amount of addition is less than 5 parts by mass, the effect of addition may not be achieved. On the other hand, if the amount of addition exceeds 100 parts by mass, the amount of addition may be too large, and the adhesion may be reduced.
[0062] The aqueous resin composition of the present invention can be suitably used as a paint, ink, adhesive, sealant, primer, etc. for various polyolefin substrates including polypropylene, but is not limited to these substrates. For example, it can be applied to other plastics, wood, metal, etc. Examples of polyolefin substrates include films, sheets, molded bodies, etc. There is no particular limitation on the coating method. In addition, the coating film after coating may be dried at room temperature, but is preferably dried at 30 to 120°C, and more preferably dried at 60 to 100°C. EXAMPLES
[0063] Next, the present invention will be described in detail with reference to examples, but the present invention is not limited to these examples.
[0064] (1) Measurement of weight average molecular weight by high-temperature GPC The analysis was performed using orthodichlorobenzene as a solvent and a Waters GPC150-C Plus at 140° C. (Column: Tosoh GMH6-HT+GMH6-HTL) The weight average molecular weight was calculated using polystyrene of known molecular weight as the standard substance.
[0065] (2) Melting point measurement using a differential scanning calorimeter (DSC) In accordance with JIS K7121-2012, a DSC measuring device (manufactured by Seiko Electric Industry Co., Ltd.) is used to measure approximately 5 mg of a sample by heating and melting it at 150°C for 10 minutes, then lowering the temperature at a rate of 10°C / min and stably holding it at -50°C, and then further increasing the temperature to 150°C at 10°C / min to melt it, at which point the melting peak temperature is measured and this temperature is evaluated as the melting point.
[0066] (3) Measurement of Z-average particle size (hereinafter simply referred to as average particle size) The average particle size (Z-average particle size) was measured by intensity distribution using a dynamic light scattering method using Malvern's Zetasizer Nano-ZS Model ZEN3600. A sample of the aqueous dispersion composition with a solid content adjusted to a concentration of 0.05 g / L was measured three times at 25° C., and the average value was calculated.
[0067] Manufacturing Example 1 280g of propylene-butene copolymer (propylene content = 70 mol%, butene content = 30 mol%), 20g of maleic anhydride, 7g of dicumyl peroxide and 420g of toluene were added to an autoclave equipped with a stirrer, and after nitrogen replacement for about 5 minutes, the reaction was carried out at 140 ° C for 5 hours while heating and stirring. After the reaction was completed, the reaction liquid was poured into a large amount of methyl ethyl ketone to precipitate a resin. This resin was further washed several times with methyl ethyl ketone to remove unreacted maleic anhydride. The obtained resin was dried under reduced pressure to obtain a solid acid-modified polyolefin resin (PO-1). From the results of infrared absorption spectrum measurement, the total content of maleic anhydride and maleic acid components was 1.3 mass%. In addition, the weight average molecular weight measured by high-temperature GPC was 80,000, and the melting point measured by DSC was 70 ° C.
[0068] Manufacturing Example 2 280g of propylene-ethylene copolymer (propylene content = 94.1 mol%, ethylene content = 5.9 mol%), 14g of maleic anhydride, 5.6g of dicumyl peroxide and 420g of toluene were placed in an autoclave equipped with a stirrer, and after about 5 minutes of nitrogen replacement, the reaction was carried out at 140 ° C for 5 hours while heating and stirring. After the reaction was completed, the reaction liquid was poured into a large amount of methyl ethyl ketone to precipitate a resin. This resin was further washed several times with methyl ethyl ketone to remove unreacted maleic anhydride. After drying under reduced pressure, 280g of the obtained maleic anhydride-modified polyolefin resin and 2520g of chloroform were placed in an autoclave equipped with a stirrer, and after about 5 minutes of nitrogen replacement, the resin was heated to 110 ° C to fully dissolve the resin. Next, 1.4g of tert-butylperoxy-2-ethylhexanoate was added and a predetermined amount of chlorine gas was blown in. The reaction solvent, chloroform, was distilled off under reduced pressure and dried to obtain a solid acid-modified chlorinated polyolefin resin (CPO-1) having a chlorine content of 18% by mass, a weight-average molecular weight of 100,000, a melting point measured by DSC of 85°C, and a maleic anhydride content of 0.9% by mass.
[0069] Example 1 (Production of aqueous resin composition (a)) In a 2-liter four-neck flask equipped with a condenser, a thermometer, a stirrer, and a dropping funnel, 100 g of the acid-modified polyolefin resin obtained in Production Example 1, 46 g of cyclohexyl methacrylate, 46 g of lauryl methacrylate, 4 g of 2-hydroxyethyl methacrylate, 4 g of 4-hydroxybutyl methacrylate, 15 g of polyoxyethylene styrenated phenyl ether (manufactured by Daiichi Kogyo Seiyaku Co., Ltd., product name "Noigen EA-197", nonionic surfactant), and 1.5 g of dioctyl sodium sulfosuccinate (manufactured by Daiichi Kogyo Seiyaku Co., Ltd., product name "Neocol P", anionic surfactant) were charged and sufficiently dissolved while maintaining the temperature at 100°C. 3.2 g of N,N-dimethylethanolamine was added to this solution and stirred for 15 minutes. Next, under vigorous stirring, 500 g of deionized water previously heated to 95°C was dropped from the dropping funnel over 30 minutes to emulsify the acid-modified polyolefin resin in phase inversion. After cooling this emulsion to 80°C, nitrogen was introduced to thoroughly replace the system with nitrogen. Next, an aqueous solution of 0.6g of ammonium persulfate dissolved in 30g of deionized water was added while maintaining the temperature at 80°C, and polymerization was initiated under a nitrogen stream. The reaction was carried out at 80°C for 8 hours under a nitrogen stream, and then cooled to obtain an aqueous resin composition (a) with a resin concentration (solid content) of 30% by mass and an average particle size of the resin particles of 140 nm. The theoretical Tg of the (meth)acrylic acid ester copolymer (B) was -14.1°C.
[0070] Example 2 (Production of aqueous resin composition (b)) An aqueous resin composition (b) having a resin concentration (solid content) of 30 mass% and an average particle size of the resin particles of 160 nm was obtained in the same manner as in Example 1, except that the types of each component were changed to the composition in Table 1. The theoretical Tg of the (meth)acrylic acid ester copolymer (B) was 46.5°C.
[0071] Example 3 (Production of aqueous resin composition (c)) An aqueous resin composition (c) having a resin concentration (solid content) of 30 mass% and an average particle size of the resin particles of 180 nm was obtained in the same manner as in Example 1, except that the amounts of each component were changed to the compositions in Table 1. The theoretical Tg of the (meth)acrylic acid ester copolymer (B) was -14.1°C.
[0072] Example 4 (Production of aqueous resin composition (d)) An aqueous resin composition (d) having a resin concentration (solid content) of 30 mass% and an average particle size of the resin particles of 100 nm was obtained in the same manner as in Example 1, except that the amounts of each component were changed to those shown in Table 1. The theoretical Tg of the (meth)acrylic acid ester copolymer (B) was -14.1°C.
[0073] Example 5 (Preparation of aqueous resin composition (e)) An aqueous resin composition (e) having a resin concentration (solid content) of 30 mass% and an average particle size of the resin particles of 140 nm was obtained in the same manner as in Example 1, except that the types of each component were changed to the composition shown in Table 1. The theoretical Tg of the (meth)acrylic acid ester copolymer (B) was -35.1℃ It became.
[0074] Example 6 (Production of aqueous resin composition (f)) An aqueous resin composition (f) having a resin concentration (solid content) of 30 mass% and an average particle size of the resin particles of 130 nm was obtained in the same manner as in Example 1, except that the types of each component were changed to the composition in Table 1. The theoretical Tg of the (meth)acrylic acid ester copolymer (B) was 46.5°C.
[0075] Example 7 (Production of aqueous resin composition (g)) An aqueous resin composition (g) having a resin concentration (solid content) of 30 mass% and an average particle size of the resin particles of 180 nm was obtained in the same manner as in Example 1, except that the types of each component were changed to the composition shown in Table 1. The theoretical Tg of the (meth)acrylic acid ester copolymer (B) was 25.6℃ It became.
[0076] Example 8 (Production of aqueous resin composition (h)) An aqueous resin composition (h) having a resin concentration (solid content) of 30 mass% and an average particle size of the resin particles of 180 nm was obtained in the same manner as in Example 1, except that the types of each component were changed to the composition in Table 1. The theoretical Tg of the (meth)acrylic acid ester copolymer (B) was -7.9°C.
[0078] Example 10 (Production of aqueous resin composition (j)) An aqueous resin composition (j) having a resin concentration (solid content) of 30 mass% and an average particle size of the resin particles of 110 nm was obtained in the same manner as in Example 1, except that the types of each component were changed to the composition shown in Table 1. The theoretical Tg of the (meth)acrylic acid ester copolymer (B) was -37.9 It became ℃.
[0079] Comparative Example 1 (Production of Water-Based Resin Composition (k)) In a 2-liter four-neck flask equipped with a condenser, a thermometer, a stirrer, and a dropping funnel, 100 g of the acid-modified polyolefin obtained in Production Example 1, 90 g of toluene, 90 g of isopropyl alcohol, and 15 g of polyoxyethylene styrenated phenyl ether (manufactured by Daiichi Kogyo Seiyaku Co., Ltd., trade name "Noigen EA-197", a nonionic surfactant) were charged and thoroughly dissolved while maintaining the temperature at 100 ° C. 3.2 g of N,N-dimethylethanolamine was added to this solution and stirred for 15 minutes. Next, under vigorous stirring, 300 g of deionized water preheated to 95 ° C. was dropped from the dropping funnel over 30 minutes to emulsify the acid-modified polyolefin by phase inversion. This emulsion was cooled to 60 ° C. and desolvated under reduced pressure to obtain an aqueous resin composition (k) having a resin concentration (solid content) of 30 mass % and an average particle diameter of the resin particles of 130 nm.
[0080] Comparative Example 2 (Production of Water-Based Resin Composition (l)) An aqueous resin composition (l) having a resin concentration (solid content) of 30 mass% and an average particle size of the resin particles of 130 nm was obtained in the same manner as in Example 1, except that the types of each component were changed to the composition in Table 1. The theoretical Tg of the (meth)acrylic acid ester copolymer (B) was 78.9°C.
[0081] Comparative Example 3 (Production of aqueous resin composition (m)) An aqueous resin composition (m) having a resin concentration (solid content) of 30 mass% and an average particle size of the resin particles of 180 nm was obtained in the same manner as in Example 1, except that the types of each component were changed to the composition in Table 1. The theoretical Tg of the (meth)acrylic acid ester copolymer (B) was 21.2°C.
[0082] The meanings of the symbols in Table 1 are as follows: LMA: lauryl methacrylate (Tg = -65°C), SMA: stearyl methacrylate (Tg = 38°C), CHMA: cyclohexyl methacrylate (Tg = 66°C), MMA: methyl methacrylate (Tg = 105°C), EHMA: 2-ethylhexyl methacrylate (Tg = -10°C), HEMA: 2-hydroxyethyl methacrylate (Tg = 55°C), 4HBA: 4-hydroxybutyl acrylate (Tg = -40°C), DMAA: dimethylacrylamide (Tg = 119°C), styrene (Tg = 100°C).
[0083] [Table 1]
[0084] (1) Adhesion 2 g of propylene glycol monomethyl ether as a film-forming agent and 2 g of "Dinol 604" (manufactured by Air Products Japan Co., Ltd.) as a wetting agent were added to 100 g of the aqueous resin composition, and the mixture was stirred with a magnetic stirrer for 30 minutes. This emulsion was spray-painted onto a polypropylene plate (manufactured by Nippon Test Panel Co., Ltd.) washed with isopropyl alcohol so that the dry coating thickness was 10 μm. After drying at 80 ° C for 3 minutes, 2K urethane paint (Retan PG White III manufactured by Kansai Paint Co., Ltd.) was spray-painted as a protective film to a thickness of 40 to 50 μm. After drying at 80 ° C for 30 minutes, the plate was left for 24 hours under an atmosphere of 25 ° C and relative humidity of 60%, and this was used as a test plate. 100 squares were made on this test plate at 1 mm intervals, reaching the base material, and cellophane tape was pressed onto the squares and peeled off at an angle of 90 degrees to the coating surface three times. The results were evaluated as follows: no peeling, △, peeling on the third try, and ×, peeling by the second try.
[0085] (2) Water resistance The test plate obtained by the method (1) above was immersed in 40°C warm water for 240 hours, and then the adhesion was evaluated by the same method as in (1) above. The occurrence of blisters (floating or swelling of the coating film) was also confirmed from the appearance of the coating film. The cases where there was no peeling or blisters were evaluated as ○, cases where there was no peeling but blisters were present were evaluated as △, and cases where there was peeling were evaluated as ×.
[0086] (3) Peel strength A test plate was prepared in the same manner as in (1) above, except that a protective film was spray-coated to a thickness of 100 μm, and then left for an additional 48 hours in an atmosphere of 25°C and 60% relative humidity to obtain the test plate. Strips were cut from the test plate at 1 cm intervals, and a 50 mm, 180° peel test was performed at a speed of 50 mm / min using a tensile tester (Tensilon RTG-1310, manufactured by A&D Co., Ltd.). The stress during pulling was regarded as the peel strength, and the average value of five tests was used as the measurement result.
[0087] (4) Compatibility The aqueous resin composition was mixed with "Superflex 150HS" (polyurethane emulsion manufactured by Daiichi Kogyo Seiyaku Co., Ltd., solid content 38% by mass) and "Primal 2133" (acrylic emulsion manufactured by Rohm and Haas Japan Co., Ltd., solid content 41.5% by mass) in a solid content ratio of 1:1 by mass, and the mixture was applied to a glass plate with a 50 μm applicator and dried at 80°C for 30 minutes. The state of the glass plate after drying was visually observed, and evaluation was performed with the following criteria: ◯ if both coating films were transparent, △ if either one of the coating films became cloudy, and × if both coating films became cloudy.
[0088] (5) High resin content stability The aqueous resin compositions obtained in the above Examples and Comparative Examples were concentrated to a resin concentration of 45% by mass, and their fluidity was checked from the outside. If the composition had fluidity, it was rated as ◯, and if the composition had a significant increase in viscosity and had no fluidity, it was rated as ×.
[0089] [Table 2]
Claims
1. An aqueous resin composition comprising an acid-modified polyolefin resin (A) and a (meth)acrylic acid ester copolymer (B), The acid-modified polyolefin resin (A) contains an unsaturated carboxylic acid or an anhydride thereof in the range of 0.5 to 10 mass %, The (meth)acrylic acid ester copolymer (B) contains, as copolymerization components, a (meth)acrylic acid ester (B1) in which the ester moiety is a hydrocarbon group having 12 or more carbon atoms and a (meth)acrylic acid ester (B2) in which the ester moiety is a hydrocarbon group having 11 or less carbon atoms, the content of the (meth)acrylic acid ester copolymer (B) is in the range of 40 to 250 parts by mass relative to 100 parts by mass of the acid-modified polyolefin resin (A); a mass ratio [(B1) / (B2)] of the (meth)acrylic acid ester (B1), the ester moiety of which is a hydrocarbon group having 12 or more carbon atoms, to the (meth)acrylic acid ester (B2), the ester moiety of which is a hydrocarbon group having 11 or less carbon atoms, is within a range of 70 / 30 to 20 / 80; The content of the organic solvent in the aqueous resin composition is 0.5% by mass or less. Aqueous resin composition.
2. The aqueous resin composition described in claim 1, wherein the (meth)acrylic acid ester copolymer (B) further contains one or more polar group-containing monomers (B3) selected from the group consisting of (meth)acrylic acid esters, (meth)acrylic acid, and (meth)acrylamide, each of which contains a polar group.
3. 3. The aqueous resin composition according to claim 1, further comprising either or both of a surfactant and a basic compound.
4. An aqueous resin composition described in any one of claims 1 to 3, wherein the glass transition temperature (Tg) of the (meth)acrylic acid ester copolymer (B) is in the range of -40°C to 80°C.
5. An aqueous resin composition described in any one of claims 1 to 4, wherein the melting point of the acid-modified polyolefin resin (A) measured by differential scanning calorimetry (DSC) is 90°C or lower.
6. A coating material for a polyolefin substrate, comprising the aqueous resin composition according to any one of claims 1 to 5.
7. An ink for polyolefin substrates, comprising the aqueous resin composition according to any one of claims 1 to 5.
8. An adhesive for polyolefin substrates, comprising the aqueous resin composition according to any one of claims 1 to 5.
9. A sealing agent for polyolefin substrates, comprising the aqueous resin composition according to any one of claims 1 to 5.
10. A primer for coating a polyolefin substrate, comprising the aqueous resin composition according to any one of claims 1 to 5.
Citation Information
Patent Citations
Coating composition for polyolefin base and application of the coating composition
JP2002188042A
Water-based coating resin composition for polyolefin substrate
JP2004256577A
Aqueous emulsion
JP2011016992A
Method of manufacturing acid-modified polyolefinic resin aqueous dispersion
JP2012219123A
Carbon fiber bundle, its manufacturing method, carbon fiber chop, carbon fiber-reinforced thermoplastic resin and molded article
JP2014051757A